2013
DOI: 10.1177/0961203313486949
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic drug monitoring of mycophenolate mofetil for the treatment of severely active lupus nephritis

Abstract: MPA-C1 may be a practical monitoring of MPA levels in patients with LN. It is convenient to monitor and may facilitate an optimum estimate of MPA exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…It is worth mentioning that the main limitation of the majority of the studies, 10,11,[27][28][29][30][31] with exception of the study conducted by Zahr et al, 9 is the small sample size that ranges from 5 to 34 patients. Moreover, although free MPA fraction is pharmacologically active, none of the studies conducted so far has determined the free fraction of MPA.…”
Section: Correlation Between Mpa Pharmacokinetics and Renal Response mentioning
confidence: 96%
See 1 more Smart Citation
“…It is worth mentioning that the main limitation of the majority of the studies, 10,11,[27][28][29][30][31] with exception of the study conducted by Zahr et al, 9 is the small sample size that ranges from 5 to 34 patients. Moreover, although free MPA fraction is pharmacologically active, none of the studies conducted so far has determined the free fraction of MPA.…”
Section: Correlation Between Mpa Pharmacokinetics and Renal Response mentioning
confidence: 96%
“…These results were further explored by the same study group. Kittanamongkolchai et al 28 determined that MPA C 1 may constitute a practical tool for monitoring the patients' exposure on MPA because 78% of patients achieved the target MPA AUC 0-12 h level of 45 mg$h$L 21 when the MMF dosage was so adjusted as to reach MPA C 1 concentration of more than 13 mg/L. Even when MPA AUC 0-12 h target level was not achieved, it was close to the target only if MPA C 1 target has been reached.…”
Section: Correlation Between Mpa Pharmacokinetics and Renal Response mentioning
confidence: 99%
“…The results also highlighted the importance of socioeconomic issues in health care access and delivery in Asian countries. Also, studies in Thai patients have shown that there was a marked interindividual difference in MPA metabolism and that drug exposure was related to therapeutic response [73,74]. In this regard, there are ongoing studies on the pharmacokinetics and pharmacogenomics of MPA in different Asian populations.…”
Section: Discussionmentioning
confidence: 99%
“…[150][151][152] Treatment to a 1 h post-dose target level of mycophenolic acid >13 mg/l resulted in a response rate of 89% in 19 patients with class III or IV lupus nephritis. 153 Further investigation is required to establish whether measurement of blood drug levels at a single time point can replace area-underthe-curve analysis, and to establish what drug level is necessary to ensure efficacy during different phases of treatment. Notwithstanding these uncertainties, research to date suggests that drug level monitoring should have a role in improving the outcomes of patients treated with mycophenolic acid based medications.…”
Section: Induction Treatmentmentioning
confidence: 99%